AD, Volume 13, n° 1, 1988 - Full Issue - journal system, (Africa Development, 1988)
Table of Contents The Road to Crisis, Adjustment and De-Industrialisation: The African Case Thandika Mkandawire .......................... 5 The Crisis of Underdevelopment and the Transition to Civil Rule: Conceptualising the Question of Democracy in Nigeria Yusuf Bangura ............................... 33 Crise et Recul du Nationalisme Economique d'Etat Collectif en Afrique Bernard Founou-Tchuigoua ................... 51 Political Instability and the Prospects for Democracy in Africa P. Anyang Nyong'o ............................ 71 Réflexion sur la Fonction Objectifs de l'Entreprise Amadou Lamine Dia .......................... 87 Coping with the Effects of the 1982-83 drought in Ghana: the view from the village George J. S. Dei ............................... 107 Publications Received ......................... 123 Index to Volume XII (1987) ....................... 127